12 escultores en la argentina. - Bértola, Elena; Glusberg, Jorge (Buenos Aires : Asociacion Internacional de Criticos de Arte, 1979)
Badii, Libero ; Bedel, Jacques ; Curatella Manes, Pablo ; Distefano, Juan Carlos ; Gomez, Norberto ; Velasco, Heras ; Heredia, Alberto ; Iommi, Ennio ; Paparella, Aldo ; Pujia, Antonio ; Renart, Emilio ; Simon, Maria
12 escultores en la argentina, Teatro Municipal General San Martin, Sala Carlos Morel, Agosto 1979
boek
Keywords: Argentinië